A MODERN APPROACH TO COLORIMETRIC CONTROL OF LIQUID PRODUCTS - Rajabova, Mahfuza (Techscience uz - Topical Issues of Technical Sciences, 2025)
This paper considers modern methods of colorimetric control of liquid food products. Particular attention is paid to spectrophotometric approaches that provide high accuracy, reproducibility, and the possibility of analysis automation. Examples of the use of spectrophotometry in the quality control of cottonseed oil are presented. The advantages of spectrophotometric analysis and the directions for its further development are formulated.